An observational study to determine the effectiveness of treatment of dental caries in management of non-specific recurrent/chronic pharyngitis - U., Jagadeeswaran V.; Marthandam, Jagadeesh; Kumar, Sathish (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Chronic pharyngitis is a common inflammatory condition of the pharynx, which has long duration and various etiological factors attributed to it. The most common local constant source of infection causing chronic pharyngitis are rhinitis, sinusitis and laryngopharyngeal reflux. The management for the above etiology is mostly symptomatic. In majority of the cases in spite of symptomatic treatment there is no relief for the patient and the non- specific conditions have to be considered in those cases. One such non-specific condition is chronic dental caries due to poor oral dental hygiene. Methods: A prospective observational study was carried out in the ENT and dental department for over a period of one year at our tertiary care hospital after obtaining institutional ethical committee clearance. Results: 50 out of the 67 patients who had chronic dental carries and who were on chronic medication for non-specific chronic pharyngitis benefitted from dental treatment. Conclusions: Patients with long duration medication for symptomatic treatment of non-specific chronic pharyngitis, if presented along with chronic dental carries, it’s recommended to do initial treatment for dental caries management. Awareness has to be created among all individuals about oral dental hygiene.